Subjective and Objective Competence Assessments in Wound Care - Stolt, Minna (Springer, 2025)
Competence assessment in wound care is important to provide safe and accurate care for patients with wound. There are many kinds of wounds, including acute and chronic wounds, of which care is complex and requires both theoretical and practical competence from healthcare professionals. Assessing competence in clinical nursing and nursing education is crucial for patient safety, costs and sustainability. Competence assessment can be either subjective, based on a person’s own judgement, or objective, based on predefined criteria or attributes. The Chapter examines subjective and objective competence assessments in the context of wound care from a theoretical perspective. The Chapter provides definitions of subjective and objective competence assessments and describes examples of competence assessment in wound care based on the literature. The subjective competence assessment in wound care research is divided into competence self-assessment of competence and attitude assessment. The objective competence assessment can be divided into theoretical competence, measured by knowledge tests, and practical performance, which includes observation and simulations. Wound care is a main competence area in nursing with a strong need for evidence-based and robust assessment.
Wound Care Education in Nursing : A European Perspective